2011
DOI: 10.1080/10803548.2011.11076907
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety of Farmers in the Vegetable Industry

Abstract: farmers pesticide exposure pesticide-related problems geographic information system pesticide residue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Work related injury is comparatively more among floriculturist than vegetable farmers which can be explained with the type of plant they are growing which in this case is rose. (Lu, 2011) The prevalence of use of personal protective equipment was very low in our study. Similar findings are seen in a study done to assess the pattern of personal protective equipment for safe use of pesticides among agricultural workers in India.…”
Section: Spraying and Personal Protective Equipment Usagecontrasting
confidence: 52%
“…Work related injury is comparatively more among floriculturist than vegetable farmers which can be explained with the type of plant they are growing which in this case is rose. (Lu, 2011) The prevalence of use of personal protective equipment was very low in our study. Similar findings are seen in a study done to assess the pattern of personal protective equipment for safe use of pesticides among agricultural workers in India.…”
Section: Spraying and Personal Protective Equipment Usagecontrasting
confidence: 52%
“…Figure 4
Figure 4 Concentration of pesticide residues (mg/kg × 0.01) in soils, vegetables, fruits, and widely used grains 10 , 11 , 12 ) .
shows the prevalence of pesticide residues in soil, fruits, vegetables and widely used grains.…”
Section: Resultsmentioning
confidence: 99%
“…Lu also reported that soil contamination with organochlorine pesticides such as endosulfan has aroused worldwide concerns considering their high toxicities and long-term persistence. Another study of Lu reported that vegetables, primarily those that are from Benguet were detected for the presence of pesticide residues 10 ) . Pesticide residue in the vegetable samples was found in 16.67% of the total samples submitted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations